The experience of occupational psychosocial stress among librarians in three African countries. Issue 6 (12th August 2019) - Agyei, Dominic Dankwah; Aryeetey, Faustina; Obuezie, Adaora Chigozie; Nkonyeni, Sixolile
Abstract : Purpose: The purpose of this paper is to focus on describing the experience of occupational psychosocial stress among librarians in Ghana, Nigeria and South Africa. It further seeks to identify the various psychosocial stress components and how they interact to determine the stress level of librarians. Design/methodology/approach: Using the Effort-Reward Imbalance scale, this descriptive study employed a web-based data collection tool (Google Form) to design and solicit data from respondents. Convenient sampling technique was used to employ 153 librarians from Ghana, Nigeria and South Africa with at least a diploma in any library-related programme, who work in either academic, public or special libraries. Findings: This study established the prevalence of occupational psychosocial stress among librarians from Ghana, Nigeria and South Africa. It was realised that gender, country of residence of respondents, age, work experience, workers with children under 13 years of age and work roles were the main factors that influenced the occupational stress among the respondents. Research limitations/implications: The response rate for this study was low. As a result, undertaking any inferential statistics to explain relationships was not possible. Originality/value: The value of this study lies in the depth of narrative data collected and the insight it affords with regards to contemporary work within libraries in Africa and beyond. The results presented may provide both a starting point for further discussion and may also promote an increased openness about issues of employee safety in the library environment.